2023
DOI: 10.1007/s40618-023-02156-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone health and body composition in transgender adults before gender-affirming hormonal therapy: data from the COMET study

C. Ceolin,
A. Scala,
M. Dall’Agnol
et al.

Abstract: Purpose Preliminary data suggested that bone mineral density (BMD) in transgender adults before initiating gender-affirming hormone therapy (GAHT) is lower when compared to cisgender controls. In this study, we analyzed bone metabolism in a sample of transgender adults before GAHT, and its possible correlation with biochemical profile, body composition and lifestyle habits (i.e., tobacco smoke and physical activity). Methods Medical data, smoking habits, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Similar results related to the levels of PA in transgender samples were also found in another studies. In the recent work by Ceolin and colleagues [53], the transgender individuals reported values of PA between 525.00 and 2772.00 METS, with no statistically relevant differences between the trans and cis sample. Data from the Minnesota Transgender Youth Survey also revealed that the majority of individuals (50.2%) are physically active for at least 60 min on 3 or more days per week [54].…”
Section: Physical Activitymentioning
confidence: 88%
“…Similar results related to the levels of PA in transgender samples were also found in another studies. In the recent work by Ceolin and colleagues [53], the transgender individuals reported values of PA between 525.00 and 2772.00 METS, with no statistically relevant differences between the trans and cis sample. Data from the Minnesota Transgender Youth Survey also revealed that the majority of individuals (50.2%) are physically active for at least 60 min on 3 or more days per week [54].…”
Section: Physical Activitymentioning
confidence: 88%
“…A recent trial, the COMET study [97], collected an extensive set of parameters, spanning from clinical and laboratory data (such as phospho-calcic and hormonal blood tests and densitometric variables) to lifestyles (including smoking habits), in a sample of 125 transgender individuals (78 assigned females at birth and 47 assigned males at birth) before gender-affirming hormone therapy initiation. According to its findings, 14.3% of the transgender sample (versus 6.2% of controls matched by sex assigned at birth and age) reported low bone mineral density, which was found to be due to body composition and lifestyle factors.…”
Section: Orthopedic Management Of Gender-diverse Individualsmentioning
confidence: 99%